AB0568 Know your vaccines – a clinical audit on the uptake of vaccinations in systemic lupus erythematosus patients. (12th June 2018) - Varughese, E.E.; McCartney, M.; Sunmboye, K.; Shaffu, S.
Abstract : Background: Systemic Lupus erythematous (SLE) is a multi-system autoimmune disease with an increased mortality and morbidity rate compared to the controlled population. One of the commonest causes of mortality and morbidity in SLE is infection. This is a result of not only the immunosuppressive effect of the disease process itself but also treatment involving disease modifying anti-rheumatic drugs (DMARDs). In fact, corticosteroids and immunosuppressants increase the risk of opportunistic infection, in addition to the more common pathogens. Vaccines provide long lasting protective immunity against microbial pathogens and prevent clinically relevant infections. Recommended vaccinations in SLE patients include H. Influenza, Pneumococcal, Hepatitis A and B, and Human Papilloma Virus (HPV). Influenza vaccines are given annually and a Pneumococcal booster dose is given at 5 years following the initial vaccine. Objectives: To assess whether, in routine clinical practise, patients with SLE are immunised against preventable disease according to EULAR recommendations and to assess the level of patient awareness. Methods: A questionnaire was designed to assess the degree of compliance with current recommendations adapted from the EULAR-recommended vaccinations in patients with autoimmune inflammatory rheumatic diseases on DMARD therapy. The questionnaire enquired into the awareness and uptake of the influenza B, pneumococcal and hepatitis B vaccines. They were sent out by postal mail, with an enclosed stamped address envelope, to all SLE patients within the university hospitals of Leicester (UHL) NHS trust identified via the rheumatology patient database. Questions included awareness of the need to have vaccinations whilst on DMARDs. The audit was conducted over a three month period and the results were compiled in Microsoft excel. Results: Of the 396 SLE patients within UHL, 86 responded. Among the patients studied 38% were on DMARD therapy, an equal proportion claimed they were not and 23% were unclear if they were on DMARD therapy. Approximately 60% were unaware of the need for vaccinations and only 27.9% acknowledged awareness for the need of the 3 vaccines mentioned above. Fifty-six (60%) patients had the influenza vaccine yet only 26 (28%) and 15 (21.8%) had the Pneumococcal and Hepatitis vaccines respectively. Conclusions: The increased infection rate in SLE can be reduced through vaccination. This highlights the importance of increasing both physician and patient awareness. Although the sample size was small, the above audit has revealed that current local practice, with regards to ensuring that all SLE patients are appropriately vaccinated, requires improvement. This can be achieved through patient and healthcare worker education, and also creating a checklist that can be added to the clinic notes. Working together with our primary care colleagues will also help bridge the divide between compliance and non-compliance. Such measures will aim to improve mortality and morbidity in SLE patients. References: [1] www.lupusuk.org.uk/bsr-guidelines/ [2] www.rheumatology.org.uk/Knowledge/Excellence/Guidelines [3] www.hss.edu/conditions_vaccinations-lupus-update.asp [4] http://ard.bmj.com/content/75/suppl_2/771.2 [5] http://ard.bmj.com/content/annrheumdis/70/3/414.full.pdf Disclosure of Interest: None declared